HUBUNGAN ANTARA PENGETAHUAN IBU NIFAS TENTANG PERSONAL HYGIENE PADA LUKA PERINEUM DENGAN PENYEMBUHAN LUKA FASE PROLIFERASI DI WILAYAH KERJA PUSKESMAS JENGGOT KOTA PEKALONGAN TAHUN 2013 - Siti I'anah; Mardi Hartono; Supriyo . (LPPM Universitas Pekalongan, 2014)
One of the causes of postpartum maternal death is if the infection does not get help, can progress to sepsis. The support factors infection genetalia in the community among many others puerperal women do not pay attention to hygiene in the injured area perineumnya, because to puerperal women, especially from the middle and lower economic circles have less knowledge in performing personal hygiene. Knowledge of the importance of personal hygiene in the perineal wound is very supportive of the wound healing process so that the infection can be avoided. This study was conducted to determine the relationship between postpartum maternal knowledge about personal hygiene with the proliferative phase of wound healing in Community Health Centre Jenggot Pekalongan in 2013. This research uses a descriptive design with cross sectional correlation. Sampling was carried out by means of the total population that is all postpartum women with perineal wound suturing is done well or not done or not done suturing to 40 people 5-20 days postpartum mothers. Collecting data using a questionnaire. Analysis of data used to test bivariate analysis spearmen's Rank. These results indicate that the respondent has knowledge of personal hygiene in good perineal wound 18 people (45.0%), sufficient knowledge of 18 people (45.0%), experienced a proliferation phase of wound healing, (ρ: 0.006 <α 0.05 ) This shows that there is a relationship between knowledge of the proliferative phase of wound healing. The conclusion that can be drawn is that there is a relationship between postpartum maternal knowledge about personal hygiene in the perineal wound with the proliferative phase of wound healing. It is therefore expected to continue to support new mothers of activities performed by midwives, especially counseling about personal hygiene during parturition with a midwife went to get more information about personal hygiene in the perineal wound.Keyword :Konowledge, personal hygiene, the proliferative phase of wound healing Library :19 books (2002-2012), 3 websites, 4 journal, scientific papers 1